QUALITY CONTROL ANALYSIS OF BROCADE FABRIC PRODUCTS USING THE SIX SIGMA METHOD AT PT X IN CIMAHI CITY - Sinta Widara; Eka Ludiya (Universitas KH. Abdul Chalim Mojokerto, 2026)
In the manufacturing industry, product quality is one of the most crucial factors in maintaining competitiveness and customer satisfaction. Increasingly intense competition, both in domestic and international markets, requires companies to consistently deliver high-quality products at efficient costs. Therefore, quality control has become a critical aspect of the production process. Companies that successfully implement effective quality control systems are able to sustain their competitiveness, even in highly competitive global markets. The textile industry is one of the sectors that continues to grow and makes a significant contribution to the national economy. PT X is a company engaged in the textile industry, particularly in the production of knitted fabrics and brocade fabrics. In practice, the brocade fabric production process still encounters various types of defects that have the potential to reduce product quality. This study aims to evaluate the implementation and planning of quality control for brocade fabric products and to analyze quality control improvement and development efforts using the Six Sigma method with the DMAIC approach (Define, Measure, Analyze, Improve, and Control). The research method employed is qualitative, with data collection techniques including interviews, observations, and documentation. Data validity and reliability were tested using source, technique, and time triangulation. The results indicate that the implementation of quality control at PT X has been carried out in accordance with the established plans; however, the application of Six Sigma has not been fully optimized, particularly at the improve and control stages. Therefore, continuous improvement efforts are required through the standardization of standard operating procedures (SOPs), operator training, machine maintenance, and regular quality monitoring to ensure consistent brocade fabric quality.